O comportamento informacional de docentes da pós-graduação da UFSM - Machado, Maria Elizete Barbosa (2021)
The present investigation, linked to the Post-Graduation Network Program whose research line is Management of Educational Technologies in Network, sought to investigate the informational behavior of UFSM Post-Graduation teachers linked to three programs. The research observed the search for and use of information on the web and in the university libraries of the same institution. The objectives were: a) to identify the profile of the professors; b) to list the most used sources of information; c) to identify reasons for success and failure in information searches; d) to find out how the searches and the use of information are carried out; e) to compare the informational behavior of the professors of the three programs; f) to create a technical report as the resultant product of the research. It is a case study and the methodology adopted is based on an applied research of exploratory-descriptive character and of mixed quali-quantitative approach. It had as a research instrument the application of a questionnaire, with closed and open questions, to the professors of the Postgraduate programs of the courses of Letters, Chemistry and Educational Technologies in Network. The intentional research sample aimed to interpret the searches, the use of information, and to find evidence of new sources of information used by the post-graduate teaching group at UFSM. The results of the research showed that the graduate teachers recognize informal databases as a source of information, but the research did not reveal whether these sources are used in research, they start their searches usually by the Google Scholar metasearch engine, blogs are not used as a source of scientific information by most of the study participants, they do not have the habit of consulting library catalogs, the high cost of access to international and national databases is a problem and few participants showed they use the specialized databases within their area of work. It was observed that information literacy as continuous learning would be an excellent option for the whole academic community, as well as the continuous training of teachers in the use of general and specialized databases. The data collected in this study will be useful for information professionals regarding the updating and adequacy of training, directing users to research needs.